Fabrication techniques for developing a functional microfluidic glass device suitable for detection in optical spectroscopy system - Rojas Rojas, Laura (2012)
Microfluidic devices offer the chance to manipulate and analyze fluids including bioassays and chemical reactions. In this study, a method to develop a microfluidic analysis system is proposed for detection of nanotubes by a Raman acquisition setup. Microchannels where fabricated in sodalime glass substrate by MeV ion beam lithography or electron beam lithography and wet etching. Fusion bonding (550 °C) was used to seal the microchannels. As a result a prototype microfluidic device with 1.6 µm deep channel that exhibit efficient sealing and suitable channel geometry was obtained. The microfluidic device was tested in a Raman spectroscopy detection system and the collected spectra showed the presence of carbon nanotubes within the channel with clear RBM and G-band peaks. By this approach a practical and simple fabrication technique for microfluidic devices combined with Raman spectroscopy was done. This device can be enhanced to perform concentration maps within the channel and further research can focus on performing steady constant fluid flow inside the channel.